2016
DOI: 10.1039/c6nr01911k
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer graphene sensing enabled by the strong Fano-resonant metasurface

Abstract: Recent advances in graphene photonics reveal promising applications in the technologically important terahertz spectrum, where graphene-based active terahertz metamaterial modulators have been experimentally demonstrated. However, the sensitivity of the atomically thin graphene monolayer towards sharp Fano resonant terahertz metasurfaces remains unexplored. Here, we demonstrate thin-film sensing of the graphene monolayer with a high quality factor terahertz Fano resonance in metasurfaces consisting of a two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…Despite this high contrast ratio, the required switching voltage may still be too high. Following this work, more efforts have also been made to achieve an efficient and fast modulation on the amplitude or phase of transmissions, reflections and even beam deflections from NIR to THz regimes . Kim et al experimentally demonstrate a metasurface combined with a graphene layer, as depicted in Figure d .…”
Section: Tuning Via Free‐carrier Effectsmentioning
confidence: 96%
“…Despite this high contrast ratio, the required switching voltage may still be too high. Following this work, more efforts have also been made to achieve an efficient and fast modulation on the amplitude or phase of transmissions, reflections and even beam deflections from NIR to THz regimes . Kim et al experimentally demonstrate a metasurface combined with a graphene layer, as depicted in Figure d .…”
Section: Tuning Via Free‐carrier Effectsmentioning
confidence: 96%
“…In such a scenario, interaction with the near-field of resonant structures (typically metallic) could prove useful in improving the sensitivity. [154][155][156] It is well known that graphene can support terahertz plasmons with a high degree of confinement (as compared to metals at the same frequencies). [146][147][148][149] Similarly, terahertz nanoantennas have been successfully employed for the detection of antibiotics, sugars, and RDX molecules.…”
Section: Sensing and Spectroscopy Of Moleculesmentioning
confidence: 99%
“…They have been widely applied to control the radiations in the optical, infrared, terahertz and microwave ranges [2][3][4][5][6][7][8][9][10][11]. In the terahertz band, extensive studies on functional metamaterial devices have been well demonstrated, including invisibility cloaks, sensors, lenses, filters, modulators, etc [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In a general way, the essential rule for designing metamaterials is to build up certain resonance modes in the unit cell, such as inductor-capacitor circuit (LC) resonance, Fano resonance, dipolar resonance, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The Fano resonance is generally derived from asymmetric spit-ring resonators (TASRs), which can support extremely high-quality (Q) factor resonances with low radiative losses [27,28]. The dipolar resonance can be directly excited by the external electromagnetic wave, and usually exhibit a robust resonance which is hardly to be altered [15]. However, these studies mainly focus on independent resonance and rarely consider the resonance switching effect.…”
Section: Introductionmentioning
confidence: 99%